Noninvasive Monitoring of Immune Rejection in Face Transplant Recipients - Kueckelhaus, Maximilian; Imanzadeh, Amir; Fischer, Sebastian; Kumamaru, Kanako; Alhefzi, Muayyad; Bueno, Ericka; Wake, Nicole; Gerhard-Herman, Marie D; Rybicki, Frank J; Pomahač, Bohdan (Plastic and reconstructive surgery, 2015)
BACKGROUND: Chronic rejection leading to allograft loss remains a significant concern after facial allotransplantation. Chronic rejection may occur without clinical signs or symptoms. The current means of monitoring is histologic analyses of allograft biopsy specimens, which is both invasive and impractical. Prior data suggest that chronic rejection is associated with changes in intima and media thickness of vessels in arms and solid organ allografts; such data have not been published for face transplant recipients. METHODS: The authors used a 48-MHz transducer to acquire images of the bilateral facial, radial, dorsalis pedis and, if applicable, sentinel flap arteries in five face transplant recipients (8 months to 4.5 years after transplantation) and five control subjects. The authors assessed the intima, media, and adventitia thickness plus lumen and the total vessel diameter and area. RESULTS: Face transplant recipients had thicker intima in all sites compared with controls, but the ratio of the intimal thickness of facial and radial arteries was similar in face transplant recipients compared with controls (1.00 versus 0.95; p = 0.742). Intraobserver correlation showed reliable reproducibility of the measurements (r = 0.935, p ≤ 0.001). Interobserver correlation demonstrated reproducibility of intima measurements (r = 0.422, p ≤ 0.001). CONCLUSION: The authors demonstrate that ultrasound biomicroscopy is feasible for postsurgical monitoring, and have developed a new benchmark parameter, the facial artery-to-radial artery intimal thickness ratio, to be used in future testing in the setting of chronic rejection. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, IV.